2019
DOI: 10.3389/fgene.2019.01224
|View full text |Cite
|
Sign up to set email alerts
|

GWAS-Assisted Genomic Prediction to Predict Resistance to Septoria Tritici Blotch in Nordic Winter Wheat at Seedling Stage

Abstract: Septoria tritici blotch (STB) disease caused by Zymoseptoria tritici is one of the most damaging diseases of wheat causing significant yield losses worldwide. Identification and employment of resistant germplasm is the most cost-effective method to control STB. In this study, we characterized seedling stage resistance to STB in 175 winter wheat landraces and old cultivars of Nordic origin. The study revealed significant (p < 0.05) phenotypic differences in STB severity in the germplasm. Genome-wide association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
73
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 55 publications
11
73
1
Order By: Relevance
“…Therefore, resistance QTL may require prioritising for selection through successive cycles of breeding. Approaches such as genomic selection could be useful for quantitative resistance by estimating a line's breeding value using genome-wide markers, and QTL identified here and in other studies can be used as fixed effects during genomic selection [75,102]. For instance, the prediction accuracy for STB resistance in wheat has been previously reported to have improved from 0.47 (without using QTL as fixed effects) to 0.62 (with using QTL as fixed effects) [75].…”
Section: Breeding For Durable Stb Resistancementioning
confidence: 85%
See 2 more Smart Citations
“…Therefore, resistance QTL may require prioritising for selection through successive cycles of breeding. Approaches such as genomic selection could be useful for quantitative resistance by estimating a line's breeding value using genome-wide markers, and QTL identified here and in other studies can be used as fixed effects during genomic selection [75,102]. For instance, the prediction accuracy for STB resistance in wheat has been previously reported to have improved from 0.47 (without using QTL as fixed effects) to 0.62 (with using QTL as fixed effects) [75].…”
Section: Breeding For Durable Stb Resistancementioning
confidence: 85%
“…Approaches such as genomic selection could be useful for quantitative resistance by estimating a line's breeding value using genome-wide markers, and QTL identified here and in other studies can be used as fixed effects during genomic selection [75,102]. For instance, the prediction accuracy for STB resistance in wheat has been previously reported to have improved from 0.47 (without using QTL as fixed effects) to 0.62 (with using QTL as fixed effects) [75]. Ultimately, a pyramiding of qualitative and quantitative resistance has been highlighted as a strategy to extend the life of resistant cultivars [103], thereby providing multiple barriers against STB and reducing the number of asexual cycles in the field during the cropping season.…”
Section: Breeding For Durable Stb Resistancementioning
confidence: 98%
See 1 more Smart Citation
“…A simulation study demonstrated that it improved prediction accuracy in the RR-BLUP model to include quantitative trait nucleotides, each explaining at least 10% of the genetic variance (Bernardo 2014). Real traits also demonstrated the same trend (Odilbekov et al 2019).…”
Section: Various Approaches To Incorporate Validated Mutationsmentioning
confidence: 90%
“…Besides enhancing prediction accuracy, GS + GWAS does not require additional data because the same phenotypic and genotypic data set is used, and it can be more accessible to breeders as it does not require extensive knowledge of the underlying genetics of a trait of interest [68]. The benefits of integrating GWAS with GS to further improve the accuracy of GS in wheat are confirmed for rusts [69,70], Septoria tritici blotch [71,72], and yield [73]. Particularly, Daetwyler et al [69] and Rutkoski et al [70] demonstrated the advantage of including markers linked to large to moderate effect genes or loci previously found to affect the traits of interest.…”
Section: Strategies For Improving Gs Prediction Accuracymentioning
confidence: 95%